2008
DOI: 10.1099/jmm.0.47339-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the antimicrobial activity of local anaesthetics used for dental analgesia

Abstract: Seven local anaesthetics and their active anaesthetic components [Ultracaine D-S (articaine hydrochloride), Carbostesin (bupivacaine hydrochloride), Scandicaine (mepivacaine hydrochloride), Xylonest (prilocaine hydrochloride), Xylocaine (lidocaine hydrochloride), Hostacaine (butanilicaine phosphate) and Novocaine (procaine hydrochloride)] were tested for their antimicrobial activity against 311 bacterial strains from 52 different species and 14 Candida albicans strains. The tested pathogens were members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…This finding has been repeated in investigations of microbial survival in other types of medication (57). Many of the candidate studies from our literature review examined the antimicrobial activity of bupivacaine at temperatures which were substantially higher than room temperature (14,33,39,(48)(49)(50)(51)(52)(53)(54). In the only study which did observe the antimicrobial activity of bupivacaine at room temperature, the local anaesthetic was found to have generally poor antimicrobial effectiveness (34).…”
Section: Effect Of Temperature On the Antibacterial Activity Of Bupivmentioning
confidence: 94%
See 3 more Smart Citations
“…This finding has been repeated in investigations of microbial survival in other types of medication (57). Many of the candidate studies from our literature review examined the antimicrobial activity of bupivacaine at temperatures which were substantially higher than room temperature (14,33,39,(48)(49)(50)(51)(52)(53)(54). In the only study which did observe the antimicrobial activity of bupivacaine at room temperature, the local anaesthetic was found to have generally poor antimicrobial effectiveness (34).…”
Section: Effect Of Temperature On the Antibacterial Activity Of Bupivmentioning
confidence: 94%
“…All have suggested that this activity is concentration-dependent (14,33,34,39,(48)(49)(50)(51)(52)(53)(54), however there is conflicting evidence as to the specifics of bupivacaine's antimicrobial activity. Some suggest that bupivacaine has good action against a variety of pathogens at clinically significant concentrations (14,50,51,54).…”
Section: Findings Of Previous Investigations Into the Antibacterial Amentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the MBC, about 10 μL of broth from those tubes which did not exhibit any visible growth in the MIC assay was cultured on freshly prepared sterile MullerHinton agar and then incubated at 37 °C for 18-24 h. after incubation the highest dilution (least concentration) that inhibited colony formation on solid medium was consider as MBC 25 .…”
Section: Determination Of Minimum Bactericidal Concentration (Mbc)mentioning
confidence: 99%